2018
DOI: 10.4103/sjg.sjg_29_18
|View full text |Cite
|
Sign up to set email alerts
|

The role of the PLR–NLR combination in the prediction of the presence of Helicobacter pylori and its associated complications

Abstract: Background/Aim:The aim of this study was to investigate the role of the platelet-to-lymphocyte ratio (PLR)–neutrophil-to-lymphocyte ratio (NLR) combination, in the prediction of the presence of Helicobacter pylori (HP) and its associated complications in the gastrointestinal system.Patients and Methods:In all, 1289 patients who underwent esophagogastroduodenoscopy and biopsy for HP were included in the study.Results:The ratio of patients with moderate and severe chronic gastritis was higher in HP (+) group tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
(24 reference statements)
0
12
0
2
Order By: Relevance
“…[42] In addition, a more recent study underlined that the combination between NLR and platelet to lymphocyte ratio might an even better predictor of HP infection and its related gastrointestinal complications than NLR alone. [43]…”
Section: Discussionmentioning
confidence: 99%
“…[42] In addition, a more recent study underlined that the combination between NLR and platelet to lymphocyte ratio might an even better predictor of HP infection and its related gastrointestinal complications than NLR alone. [43]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent paper showed that the combination of the NLR and platelet to lymphocyte ratio might even be a better predictor of HP infection-related gastrointestinal complications than NLR alone [26].…”
Section: Discussionmentioning
confidence: 99%
“…[17] Mustafa ve ark. [18] yaptığı çalışmada HP (+) grupta öncelikle PLO ve NLO oranları ile ilişkisini incelemişler ve bu oranları daha yüksek saptamışlardır. Alt grup analizlerinde trombosit sayısı, PDW, PCT gibi trombosit indekslerini de yüksek bulmuşlardır.…”
Section: Bulgularunclassified
“…Alt grup analizlerinde trombosit sayısı, PDW, PCT gibi trombosit indekslerini de yüksek bulmuşlardır. [18] Sahwa ve ark. [19] yaptığı çalışmada, verilerimizden farklı olarak HP (+) olan hastalarda MPV'yi daha yüksek PDW'yi ise daha düşük saptamışlar ve trombosit sayısını hafif düşük bulmuşlardır.…”
Section: Bulgularunclassified